Association of enamel microabrasion and dentinal bleaching in recovering an adolescent patient's smile: a case report - Sundfeld, Renato Herman [UNESP]; Souza, Rafael Guimarães de [UNESP]; Guedes, Ana Paula Albuquerque [UNESP]; De Oliveira, Fernanda Garcia [UNESP]; Machado, Lucas Silveira [UNESP]; Rahal, Vanessa [UNESP]; Neto, Daniel Sundfeld (My University, 2010)
This article presents the enamel microabrasion protocol for removing intrinsic white stains of hard texture on the enamel surface, using a 37% phosphoric acid/pumice mixture associated with a carbamide peroxide-based bleaching agent in custom-made mouth trays. We observed that these clinical procedures were safe and effective, and solved our patient's esthetic problem. © 2010 Nova Science Publishers, Inc.